A numerical evaluation on multi-interfaced fast handoff scheme: impact of rising link switching delay for a high speed car - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Abdullah, Azween; Hasan, Mohammad Kamrul (American Scientific Publishers, 2016)
In Network Mobility (NEMO) environment, recurrent movement of a mobile router is one of the distinguished characteristics since this may affect the performance of the existing mobility management schemes. The movement pattern straightly influence once transmission links among mobile routers are established or failed, which is connected with the system topology. Therefore, numerical evaluation is a noteworthy process to apprehend the performance of any mobility management schemes as well as the constraints of emerging mobility management outcomes specifically for mobile environments. This paper proposed a numerical model to analyze the handoff performance of the multi-interfaced fast handoff scheme during movement of mobile router among different access technology in NEMO. Afterward, using numerical model, it has presented the numerical results of multi-interfaced fast handoff scheme as well as compared it with the standard Network Mobility Basic Support Protocol (NEMO BSP) and Fast NEMO (FNEMO) scheme. Two metrics such as handoff delay as well as relative gain are considered as the performance metrics in different circumstances identified by link switching delay of the mobile router. It has been perceived from the outcomes that, the multi-interfaced fast handoff scheme performs better compared to NEMO BSP and FNEMO scheme in terms of handoff delay and relative gain.